ANALISA JENIS ASAM TERHADAP KECEPATAN DESTRUKSI DAUN SINGKONG - Hulyadi, Hulyadi (Jurnal Ilmiah IKIP Mataram, 2020)
Proper sample preparation is key in sample analysis. Preparation errors will have an impact on the analysis and interpretation of data generated by certain instruments. One of the sample preparation techniques is digestion. Destruction is a treatment of breaking compounds into their elements so that they can be analyzed. The term destruction is also called overhaul, namely from metal organic forms to inorganic metals. The purpose of this study was to analyze the digestion rate of several strong acids. This research is an experimental research in the laboratory. The sample in this study was cassava leaves that were taken from the middle of the tree. The obtained data are described in graphs. Based on the research that has been done, it was found that Nitric acid (HNO3) has the fastest destructive ability compared to hydrochloric acid (HCl) and sulfuric acid (H2SO4).